Chemical Composition, Antioxidant, Antibacterial, Antibiofilm, and Cytotoxic Activities of Robusta Coffee Extract (Coffea canephora) - Erma Suryanti; Dwi Retnowati; Muhammad Eka Prastya; Novita Ariani; Indri Yati; Vera Permatasari; Tjandrawati Mozef; Indah D. Dewijanti; Apriza Yuswan; Muhammad Asril; Elisa Nurma Riana; Irmanida Batubara (HAYATI Journal of Biosciences, 2023)
Coffee extracts are a rich source of potential compounds with numerous biological activities. This study aimed to investigate the potential of chemical compounds derived from robusta coffee extract (Coffea canephora) and its dominant compound, caffeine, to scavenge free radicals, inhibit bacterial growth and biofilm formation, and cytotoxic properties in human breast adenocarcinoma cell line. Chemical constituents of coffee extract were analysed quantitively for total phenolic, flavonoid, and alkaloid contents, along with Liquid Chromatography Quadrupole-Mass Spectrometry (LC/MS–MS) analysis. Antioxidant activity was measured by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis; 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) methods. Antibacterial pair with antibiofilm properties against Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus were also determined, as well as cytotoxic activity on the MCF7 cell line model. The LC/MS–MS analysis of coffee extracts revealed high levels of caffeine; thus, the caffeine standard is used in all subsequent assays. Notably, robusta coffee extract showed remarkable antioxidant activity and selective inhibition of the growth against gram-positive and negative bacteria, along with the best inhibition of P. aeruginosa biofilm. However, compared with the caffeine standard, robusta coffee extract had lower cytotoxic activity and different bacterial targets in antibacterial and antibiofilm properties. Our results indicate that Robusta coffee extract is potentially a functional food due to its high alkaloid, phenolic, and flavonoid content and antioxidant activity, besides being used for natural compounds against bacterial infections.